Crustal architecture of the Wilkes Subglacial Basin in East Antarctica, as revealed from airborne gravity data - Jordan T. A.; Ferraccioli F.; ARMADILLO, EGIDIO; BOZZO, EMANUELE (Tectonophysics, 2013)
The Wilkes Subglacial Basin, in the hinterland of the Transantarctic Mountains, represents one of the least understood continental-scale features in Antarctica. Aeromagnetic data suggests this basin may be imposed on a Ross age back arc region adjacent to the East Antarctic Craton. However, the evolution of the deeper crustal structure is disputed. Here, we present new airborne gravity data that reveals the crustal architecture of the northern Wilkes Subglacial Basin. Our gravity models indicate that the crust under the northern Wilkes Subglacial Basin is 30–35 km thick, i.e. ca 5–10 km thinner than imaged under the Transantarctic Mountains, and ~ 15 km thinner than predicted from some flexural and seismic models in the southern Wilkes Basin. We suggest that crustal thickening under northern Victoria Land reflects Ross-age (ca 500 Ma) orogenic events. Airy isostatic anomalies along both flanks of the Wilkes Basin reveal major inherited tectonic structures, which likely controlled the basin location, supporting aeromagnetic interpretations of the Wilkes Subglacial Basin as a structurally controlled basin. The positive anomaly along the western margin of the basin defines the boundary between the East Antarctic Craton and the Ross Orogen, and the anomaly along its eastern flank likley reflect high-grade rocks of the central Wilson Terrane. Our models indicate that the crust is ~ 5 km thinner beneath the northern Wilkes Basin, compared to formerly contiguous segments of the Delamerian Orogen in south-eastern Australia. The thinner crust may be linked to: i) back-arc basin formation or orogenic collapse processes and segmentation within the Ross\Delamerian Orogen, ii) Jurassic to Cretaceous extension prior to break-up between Australia and East Antarctica, iii) Cenozoic glacial erosion or most likely, iv) a combination of these processes.